2011
DOI: 10.1038/nchem.1193
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic molecular pentafoil knot

Abstract: Knots are being discovered with increasing frequency in both biological and synthetic macromolecules and have been fundamental topological targets for chemical synthesis for the past two decades. Here, we report on the synthesis of the most complex non-DNA molecular knot prepared to date: the self-assembly of five bis-aldehyde and five bis-amine building blocks about five metal cations and one chloride anion to form a 160-atom-loop molecular pentafoil knot (five crossing points). The structure and topology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
244
0
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(251 citation statements)
references
References 45 publications
3
244
0
4
Order By: Relevance
“…For instance by mixing templates which favour the formation of trefoils and 8 19 knots, respectively, we find that pentafoil knots, practically absent in the monodisperse topological phase diagram, can now be observed. Another interesting avenue in which our work can be further pursued in the future could be to allow to for some flexibility of the templates, as would be relevant for molecular or polymeric building blocks 26 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance by mixing templates which favour the formation of trefoils and 8 19 knots, respectively, we find that pentafoil knots, practically absent in the monodisperse topological phase diagram, can now be observed. Another interesting avenue in which our work can be further pursued in the future could be to allow to for some flexibility of the templates, as would be relevant for molecular or polymeric building blocks 26 .…”
Section: Resultsmentioning
confidence: 99%
“…It may further provide a route to design novel synthetic molecular knots, if templates of small enough size can be fabricated. This would extend the current range of synthetic molecular topologies which, notwithstanding recent major technical advancements [23][24][25][26][27][28] , is still presently limited.…”
mentioning
confidence: 99%
“…Leigh and co-workers have reported the self-assembly of five bis-aldehydes, five bis-amines, five metal cations and one chloride anion to form a 160-atom covalent pentafoil knot. 71 The authors first described that the reaction of bis-aldehyde 123 and a series of amines (124a-j) in the presence of FeCl 2 in DMSO at 60 1C forms a symmetric and cyclic pentafoil knot, as confirmed by 1 H NMR and ESI-MS spectroscopy. It was found that anilines (124j) and amines with two substituents on the amine-bearing carbon atom (124h,i) could not form pentafoil knots with 123 and FeCl 2 , but all other amines tested did.…”
Section: Self-assembled and Anion Templated Molecular Architecturesmentioning
confidence: 99%
“…9 Recently, researchers have also determined facile methods to create knotted DNA via an electric field, 10,11 and this work has led to microfluidic experiments examining how the coil−stretch transition is affected by the presence of knots.…”
Section: Introductionmentioning
confidence: 99%